Role of urine reagent strips in early diagnosis of meningitis - Preeti Singh; Vijay Kumar Jaiswal; Neha Singh; Anamika Singh Thakur (Journal of Krishna Institute of Medical Sciences University)
Background: Early diagnosis of meningitis is critical to reducing associated morbidity and mortality, especially in resource-limited settings. Conventional Cerebrospinal Fluid (CSF) analysis is accurate but time-consuming. Urine reagent strips offer a rapid, bedside alternative for detecting key CSF abnormalities. Aim and Objectives: To evaluate the diagnostic accuracy of urine reagent strips (Combur 10 Test M, Roche, Germany) in detecting CSF leukocytes, glucose, and protein in patients with suspected meningitis. Material and Methods: This prospective study included 100 CSF samples from patients aged 0 to 62 years, clinically suspected of meningitis and admitted to LLRM Medical College, Meerut, between January and December 2022. CSF samples were simultaneously analyzed using standard cytobiochemical methods (gold standard) and urine reagent strips. Diagnostic performance was assessed using sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV), and accuracy. Results: Of 100 patients, 75% were children, 40% of whom were neonates. Diagnosed cases were tubercular meningitis (68%), bacterial meningitis (20%), aseptic meningitis (9%), and normal CSF (3%). The urine reagent strips had high diagnostic accuracy: leucocytes: showed sensitivity 100%, specificity 97%, accuracy 98%.Glucose had a sensitivity 97.4%, specificity 95.6%, accuracy 97% while protein had sensitivity 98.5%, specificity 79.3%, accuracy 93%. Conclusion: Urine reagent strip method is a fast, effective screening test for initial CSF analysis in suspected meningitis. The ease of use, short turnaround time, and high reliability are particularly beneficial in emergency or resource-limited settings, allowing for expedient clinical decision-making.